Implementation of Rucah Fish Meal as a Substitute for Fish Meal in the Native Chicken Ration - Nurhayati, Nurhayati; Nelwida, Nelwida; Berliana, Berliana; Lisna, Lisna; Ramadan, Fauzan (Faculty of Agriculture, 2025)
This research aims to assess the performance of native chickens fed with rucah fish meal (RFM) as a substitute for fish meal (FM). A total of 200 native chickens, aged 1 day, were maintained for 8 weeks and divided into 20 experimental units with five treatments and four replications. The treatments included substituting fish meal in the ration with rucah fish meal at various levels: P0= 12% FM and 0% RFM, P1= 9% FM and 3% RFM, P2= 6% FM and 6% RFM, P3= 3% FM and 9% RFM, and P4= 0% FM and 12% RFM. A completely randomized design was used with a coefficient of variation for initial body weight of 2.37%. Parameters measured included feed consumption, body weight, carcass percentage, and feed conversion ratio. The results showed that replacing fish meal with rucah fish meal did not significantly affect (P0.05) feed consumption but significantly increased (P0.05) chicken body weight and improved feed conversion ratio. It was concluded that fish meal can be replaced up to 100% with rucah fish meal (12% in the ration) to improve native chicken performance.